Temperature accumulation effect on roses development using generalized functional linear models (2019)
"This project proposed the study of how and when the accumulation of temperature, represented as functions, affected the expected harvest date of roses in Chía, Cundinamarca. The methodology was based on Generalized Functional Linear Models assuming that the random component followed a Gamma Distribution."--Tomado del Formato de Documento de Grado.